2021
DOI: 10.3390/life11070597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Five Polymorphisms on Percentage of Oleic Acid in Beef and Investigation of Linkage Disequilibrium to Confirm the Locations of Quantitative Trait Loci on BTA19 in Japanese Black Cattle

Abstract: Five polymorphisms associated with the percentage of oleic acid (C18:1) in beef fat were previously reported on bovine chromosome 19 in different Japanese Black cattle populations. This study aimed to verify the effects of these five polymorphisms on C18:1 using the same Japanese Black cattle population and conduct linkage disequilibrium (LD) analysis in order to determine the locations of the quantitative trait loci (QTLs). We genotyped the five polymorphisms (SREBP1 c.1065 + 83 (84bp indel), STARD3 c.1187 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…SREBP1 or also known as sterol regulatory element binding transcription factor 1 (SREBF1) is also essential in the fat metabolism of ruminants because it also influences the fat characteristics of both meat and dairy products. This has been demonstrated in cattle (Harvatine & Bauman 2006;Proskura et al 2017;Gamarra et al 2021;Kawaguchi et al 2021), buffalo (Deng et al 2017;Xu et al 2019), goat (Xu et al 2016), and sheep (Tsiplakou et al 2015;Liang et al 2020;Carcangiu et al 2021). In bovine, the SREBP1 gene is located on chromosome 19 with 21 exons and encodes 1183 amino acids (Hoashi et al 2007).…”
Section: Introductionmentioning
confidence: 92%
“…SREBP1 or also known as sterol regulatory element binding transcription factor 1 (SREBF1) is also essential in the fat metabolism of ruminants because it also influences the fat characteristics of both meat and dairy products. This has been demonstrated in cattle (Harvatine & Bauman 2006;Proskura et al 2017;Gamarra et al 2021;Kawaguchi et al 2021), buffalo (Deng et al 2017;Xu et al 2019), goat (Xu et al 2016), and sheep (Tsiplakou et al 2015;Liang et al 2020;Carcangiu et al 2021). In bovine, the SREBP1 gene is located on chromosome 19 with 21 exons and encodes 1183 amino acids (Hoashi et al 2007).…”
Section: Introductionmentioning
confidence: 92%
“…This region includes growth hormone (GH; 48.8 cM) but Taylor et al (1998) were unable to identify the other genes in BTA19 responsible for the differences in stearic and oleic acids. Kawaguchi et al (2021) reported fatty acid synthase (FASN; 51.4 cM) and sterol regulatory element-binding protein 1 (SREBP1; 35.2 cM) are located on BTA19. FASN regulates myristic acid and palmitic acid synthesis and SREPB1 is a transcription factor that regulates expression of FASN and SCD1 (located on BTA26; Campbell et al, 2001).…”
Section: Genetic Regulation Of Fatty Acid Composition In Beef Cattlementioning
confidence: 99%